BMP10 level helps to stratify risk of atrial fibrillation recurrence within one year after catheter ablation. (19th May 2022) - Zink, MD; Hermans, B; Gramlich, M; Philippens, SAM; Vernooy, K; Van Hunnik, A; Linz, DK; Zeemering, S; Schotten, U
Abstract: Funding Acknowledgements: Type of funding sources: Public Institution(s). Main funding source(s): DGK Electrophysiology grant Background: Freedom of atrial fibrillation (AF) is the main purpose of catheter ablation. However, AF recurrence is commonly seen after catheter ablation. Cardiovascular biomarkers may help to identify patients at risk for AF recurrence. Purpose: We investigated the association of preprocedural known and novel cardiovascular biomarker level with AF recurrence within one year after catheter ablation. Methods: In 187 patients of the AFAB registry (University Maastricht, the Netherlands) clinical recurrence of AF after catheter ablation was investigated using Holter ECGs at 3- and 12-months follow-up. Blood samples taken before AF catheter ablation were analyzed for prediction of AF recurrence by known or novel cardiovascular biomarkers (FGF23, BMP10, Ang2, IGFBP7, CA125, NT-proBNP, TNT_hs, sFlt_1, ESM1_7F89A5, DKK3). Recurrence of AF was defined as any symptomatic, or ECG documented episode of AF within one year after catheter ablation. A logistic regression model adjusted for typical risk factors of AF recurrence (Sex, age, type of AF (paroxysmal or persistent), ongoing rhythm, LA diameter, heart failure, body mass index and hypertension) was calculated and receiver-operating analysis was performed for prediction of AF recurrence. Results: AF recurrence was found in 86 patients within one year after catheter ablation. Elevated biomarker level in patients with AF recurrence were found for BMP10, Ang2, and NT-proBNP in univariate analysis (table 1). In the logistic regression BMP10 (Odds ratio 2.94, 95%CI 1.089-7.939, P=0.033) indicated a high probability of AF recurrence within one year. A model including factors of AF recurrence showed a predictability for AF recurrence of an area under the curve (AUC) of 0.68 (sensitivity 60%, specificity 64%). By adding each of the univariate significant biomarker the predictability of the model increases further Ang2 (AUC 0.69, sensitivity 69%, specificity 60%), NT-proBNP (AUC 0.69, sensitivity 65%, specificity 60%), and BMP10 (AUC 0.71, sensitivity 60%, specificity 73%). Conclusions: Based on our data, Ang2, BMP10, NT-proBNP showed elevated values for patients with recurrence of AF within one year before catheter ablation. BMP10, which is likely associated with trabeculation of the heart, outperformed the other investigated known and novel biomarker indicating a higher probability of AF recurrence within one year after ablation.